Nucleolar scaffold protein, WDR46, determines the granular compartmental localization of nucleolin and DDX21. (15th July 2013) - Hirai, Yuya; Louvet, Emilie; Oda, Toshiyuki; Kumeta, Masahiro; Watanabe, Yuzo; Horigome, Tsuneyoshi; Takeyasu, Kunio
<x xml:space="preserve">Abstract</x> The nuclear scaffold is an insoluble nuclear structure that contributes to the inner nuclear organization. In this study, we showed that one of the nuclear scaffold proteins, WDR46, plays a role as a fundamental scaffold component of the nucleolar structure. WDR46 is a highly insoluble nucleolar protein, and its subcellular localization is dependent on neither DNA nor RNA. The N‐ and C‐terminal regions of WDR46 are predicted to be intrinsically disordered, and both regions are critical for the nucleolar localization of WDR46 and the association with its binding partners. When WDR46 was knocked down, two of its binding partners, nucleolin and DDX21 (involved in 18S rRNA processing), were mislocalized from the granular component to the edges of the nucleoli, whereas other binding partners, NOP2 and EBP2 (involved in 28S rRNA processing), were not affected. This is because the proper recruitment of nucleolin and DDX21 to the nucleoli in daughter cells after cell division is ensured by WDR46. These findings suggest a structural role for WDR46 in organizing the 18S ribosomal RNA processing machinery. This role of WDR46 is enabled by its interaction property via intrinsically disordered regions.